An Analysis Of English Community Students' Grammatical Error In Speaking English At STAI Hubbulwathan Duri - Khairunnisa (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
This study is a quantitative approach with descriptive design. It aims to know the students’ errors in speaking. The researcher used a descriptive analysis technique with the percentage from the frequency of each type of errors that the students’ commit on their grammatical errors in speaking. The subject of this study was the student English community, while the object of this study was a students’ grammatical errors in speaking. The researcher are used random sampling. There were 20 samples from 43 populations. To collect data, researcher used speaking tests to find out grammatical errors that students made in their language skills. Based on data analysis, the researcher have found the kinds of errors students made in their speaking. The total number of errors made by the student is 93 percent blame the percentage of the student's errors in omission is 15.05% addition is 22,58% misformation 56.98%, and misordering 5.37%. So the most common students’ grammatical errors in speaking was a Misformation total of 53 errors or it was up to 56,98%